Kajian Penghematan Komsumsi Energi Dengan Menggunakan Energy Value Stream Mapping (EVSM) di Industri Otomotif - Riyadi Juhana; Muhammad Ramdhani (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Electrical waste problems often occur in the automotive industry, particularly in the vehicle painting process within the Paint Shop, which consists of Deck Cleaning Pre, Pre-Treatment & Electro Deposition (PT-ED), Dry Sanding I & UBS, Surface, Dry Sanding II, Top Coat Booth, and Paint Finishing. Estimated electrical waste occurs in PT-ED section and the oven. PT-ED comprises 9 processing tanks that often experience idle time while waiting for vehicle bodies to be processed. This situation occurs because when body 1 and body 2 are processed in PT-ED, body 1 should be in tank 4 while body 2 in tank 1. However, in implementation, body 1 is already in tank 6 while body 2 remains in tank 1, causing tanks 2 through 5 to become idle. The objective of this research is to utilize Energy Value Stream Mapping and Finite State Machine models. The results indicate that workstations in the Paint Shop still experience waste in electrical consumption. This is evidenced by the following ratios: Tva = 0.6, Tnva = 0.27, Tnva/n = 0.04, EIva = 0.55, EInva = 0.10, EInva/n = 0.35, Eva = 0.8, Enva = 0.07, Enva/n =e 0.12, Cva = 0.8, Cnva = 0.07, Cnva/n = 0.12.